Preparation and characterization of silver/chitosan/poly(ethylene glycol) nanocomposites by green route and evaluation of their antibacterial activities - Tay, Mei Yen (2013)
The aim of this study is to investigate the effect of bipolymers and stirring time in control size of nanoparticles to perform antibacterial activity. In this study, silver nanoparticles (Ag NPs) were prepared by green synthesis method using green agents, chitosan (Cts) and polyethylene glycol (PEG) at 60 ºC under different stirring times of reaction. Silver nitrate (AgNO3) was taken as the metal precursor while Cts and PEG were used as the solid support and polymeric stabilizer. After that, the properties and the size of Ag/Cts/PEG nanocomposites (NCs) were studied under different stirring times of reaction. The developed Ag/Cts/PEG NCs were then characterized by the ultravioletvisible (UV-Vis) spectroscopy, X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy dispersive x-ray fluorescence (EDXRF), fourier transform infrared (FTIR) spectroscopy and zeta potential measurement. The antibacterial effect of silver/chitosan/polyethylene glycol nanocomposites (Ag/Cts/PEG NCs) also was investigated by using Mueller-Hinton agar disc diffusion method to test against Staphylococcus aureus (S. aureus), Micrococcus luteum (M. luteum), Pseudomonas aeruginosa (P. aeruginosa) and Escherichia coli (E.coli). Formation of Ag NPs was determined by UV-Vis spectroscopy where surface plasmon absorption maxima can be observed at 415-430 nm from the UV-Vis spectrum. The synthesized nanoparticles were also characterized by X-ray diffraction (XRD). The peaks 2θ of 37.91°, 43.71°, 64.06° and 76.98° are characteristics to the (111), (200),(220), and (311) planes of the face-centered cubic (fcc) of Ag NPs, respectively. Therefore, the peaks of contaminated crystalline phases were unable to be located. Moreover, the particle size distribution also was examined the by TEM. TEM images revealed that Ag NPs synthesized were nearly in spherical shape. The average diameters of the Ag NPs prepared under the different stirring time were in the range of 5.50 nm to 18.55 nm. In addition, the optimum stirring time to synthesize the smallest particle size was 12 hrs with mean diameter of 5.50 nm. The morphology of the Ag NCs films were also characterized using SEM. SEM images showed that porosity surfaces presented under longer stirring times. The EDXRF also confirmed the presence of elemental silver and no peaks of other impurities were detected. From the FTIR spectra, it showed that molecular interaction exists between the Ag NPs with the polymeric chains. The bonding interaction present between the negatively charged oxygen from hydroxyl groups of Cts and PEG chains with the positively charged Ag NPs. The stability of particles in nanosuspension at 12 hrs of stirring times was confirmed with the zeta potential measurements. The Ag NPs in Cts/PEG were effective against all tested bacteria, Gram-positive (S. aureus and M. luteus) and Gram-negative bacteria (P. aeruginosa and E. coli). Higher antibacterial activity was observed for Ag NPs with particle sizes smaller than 10 nm. Hence, the results showed that AgNPs with 12 and 24 hrs of stirring times give a larger inhibition zones for the antibacterial test. These also suggested that Ag NPs can be employed as an effective bacteria inhibitor and can be applied in medical field. A green synthesis method had been employed to prepare the Ag NPs in Cts/PEG suspension at 60 ºC under different stirring times of reaction to examine the effect of bipolymers and stirring time in control size of nanoparticles to perform antibacterial activity.